2016
DOI: 10.1186/s12913-016-1878-4
|View full text |Cite
|
Sign up to set email alerts
|

A prospective evaluation of first people’s health promotion program design in the goulburn-murray rivers region

Abstract: BackgroundAboriginal Community Controlled Organisations (ACCOs) provide community-focussed and culturally safe services for First Peoples in Australia, including crisis intervention and health promotion activities, in a holistic manner. The ecological model of health promotion goes some way towards describing the complexity of such health programs. The aims of this project were to: 1) identify the aims and purpose of existing health promotion programs conducted by an alliance of ACCOs in northern Victoria, Aus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…However, the convenience sample did include a wide range of age groups and parents. Despite these limitations, this study adds to the body of evidence about community‐led, strength‐based health promotion for Aboriginal people in Victoria . This is important as our study found that SSB consumption among Aboriginal and Torres Strait Islander people appears to be significantly higher in Victoria compared to other states and territories.…”
Section: Discussionmentioning
confidence: 71%
“…However, the convenience sample did include a wide range of age groups and parents. Despite these limitations, this study adds to the body of evidence about community‐led, strength‐based health promotion for Aboriginal people in Victoria . This is important as our study found that SSB consumption among Aboriginal and Torres Strait Islander people appears to be significantly higher in Victoria compared to other states and territories.…”
Section: Discussionmentioning
confidence: 71%
“…Rather partners of communities should be guided by the communities themselves. For example, ecological frameworks have been successfully utilised in a number of health promotion programs run in Victoria in collaboration with Aboriginal and Torres Strait Islander health organisations [41], and could potentially be useful in the context of contraceptive practices.…”
Section: Discussionmentioning
confidence: 99%
“…There were no definitions or conceptualisation of public involvement in almost half of articles ( n = 43, 46.2%) [ 40 – 82 ]. Where reported, public participant numbers ranged from 4 [ 83 ], to an estimated 1200 [ 84 ], though no numbers were given in 13 articles (14.0%) [ 45 , 47 , 49 , 58 , 69 , 72 74 , 77 , 85 88 ], and incomplete or estimated numbers were provided in a further 25 (26.9%) [ 40 , 43 , 44 , 50 , 51 , 56 , 57 , 61 – 63 , 66 , 76 , 82 , 84 , 89 99 ]. Some authors provided demographic data of public participants, such as age, gender, medical condition and/or race, however, there was no detail provided in more than half of articles ( n = 52, 55.9%) [ 37 , 38 , 40 , 41 , 43 – 51 , 55 , 58 , 59 , 61 , 63 , 66 , 68 , 69 , 71 74 , 77 , 79 , 81 – 88 , 93 , 95 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…Evaluation of the reported outcome was outlined in less than half of studies ( n = 39, 43.3%) [ 38 , 41 45 , 47 50 , 53 , 54 , 56 59 , 61 , 65 , 66 , 68 71 , 80 , 81 , 83 85 , 87 , 92 , 93 , 99 , 102 , 105 , 107 , 109 , 110 , 123 , 131 ] (Additional file 2 ). Some evaluations were reported additionally [ 59 , 70 , 107 ] or exclusively [ 50 , 53 , 61 , 66 , 71 , 76 , 81 , 83 , 85 , 102 , 123 , 131 ] in separate publications.…”
Section: Resultsmentioning
confidence: 99%